M2 muscarinic receptor activation regulates schwann cell differentiation and myelin organization. Issue 7 (9th January 2014) - Uggenti, Carolina; De Stefano, M. Egle; Costantino, Michele; Loreti, Simona; Pisano, Annalinda; Avallone, Bice; Talora, Claudio; Magnaghi, Valerio; Tata, Ada Maria
ABSTRACT Glial cells express acetylcholine receptors. In particular, rat Schwann cells express different muscarinic receptor subtypes, the most abundant of which is the M2 subtype. M2 receptor activation causes a reversible arrest of the cell cycle. This negative effect on Schwann cell proliferation suggests that these cells may possibly progress into a differentiating program. In this study we analyzed the in vitro modulation, by the M2 agonist arecaidine, of transcription factors and specific signaling pathways involved in Schwann cell differentiation. The arecaidine‐induced M2 receptor activation significantly upregulates transcription factors involved in the promyelinating phase (e.g., Sox10 and Krox20) and downregulates proteins involved in the maintenance of the undifferentiated state (e.g., c‐jun, Notch‐1, and Jagged‐1). Furthermore, arecaidine stimulation significantly increases the expression of myelin proteins, which is accompanied by evident changes in cell morphology, as indicated by electron microscopy analysis, and by substantial cellular re‐distribution of actin and cell adhesion molecules. Moreover, ultrastructural and morphometric analyses on sciatic nerves of M2/M4 knockout mice show numerous degenerating axons and clear alterations in myelin organization compared with wild‐type mice. Therefore, our data demonstrate that acetylcholine mediates axon‐glia cross talk, favoring Schwann cell progression into a differentiated myelinating phenotype and contributing to compact myelin organization. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 676–691, 2014